Modulation of the intensity of reflected x-rays and control of its parameters in the presence of volume acoustic waves; Journal of Contemporary Physics (Armenian Academy of Sciences); Vol. 50, iss. 2 - Muradyan T. R.; Amiraghyan R. V.; Khlopuzyan S. N.; Wagner A. R. Aleksandr Rudolfovich; Kocharian (Kocharyan) V. R. Vagan Rashidovich (2015, 2015)
Title screen